Derivation and validation of a prediction model for inadequate bowel preparation in Chinese outpatients - Huifang Yin; Yan Wang; Hangfang Wang; Tian Li; Xiangxiang Xu; Fengyu Li; Lihua Huang (Scientific Reports)
Abstract The quality of bowel preparation is an important factor in the success of colonoscopy. However, multiple influencing factors that function together can lead to inadequate bowel preparation. The main objective of this study was to explore the specific factors that affect the quality of bowel preparation, with the goal of deriving and validating a predictive model for inadequate bowel preparation in Chinese outpatients. A prospective observational study. We conducted a prospective study in a tertiary hospital in Zhejiang Province that included elective colonoscopy outpatients treated between December 15, 2022 and August 12, 2023. Clinical data related to the patient characteristics and patient bowel preparation were collected to analyze the risk factors of inadequate bowel preparation in outpatients. The quality of bowel preparation was assessed by using the Boston bowel preparation scale (BBPS). Inadequate bowel preparation was defined as a total BBPS score of < 6 or any segment score of < 2. The predictive model was constructed based on multivariate logistic regression, and the discrimination and calibration of the prediction model were evaluated via internal and external validation; additionally, a clinical decision curve was drawn to evaluate the clinical utility of the model. A total of 1314 patients were included from December 15, 2022 through May 31, 2023 (derivation cohort, n = 1035) and from June 1 through August 12, 2023 (external validation cohort, n = 279). Inadequate bowel preparation occurred in 260 of 1035 patients in the derivation cohort (25.1%). Multivariate analysis identified that male sex (OR = 1.690, 95% CI: 1.242–2.300), diabetes (OR = 1.769, 95% CI: 1.059–2.954), constipation (OR = 2.375, 95% CI: 1.560–3.617), history of colorectal surgery (OR = 2.915, 95% CI: 1.455–5.840), a high fiber diet used at 24 h before examination (OR = 2.662, 95% CI: 1.636–4.334) and the time interval from the end of the bowel preparation to the start of the colonoscopy (PC) >5 h (OR = 2.471, 95% CI: 1.814–3.366) were independent risk factors. We derived a model to identify patients with inadequate cleansing by using data from patients in the derivation cohort and tested it in the validation cohort. The area under the curve (AUC) was 0.704 (95% CI: 0.667–0.741), with a calibration value of p = 0.632 in the derivation cohort. Bootstrap cross-validation showed a good model calibration condition. For the validation cohort, the AUC was 0.704 (95% CI: 0.628–0.779), and the calibration value was p = 0.376. We identified the influencing factors of outpatient bowel cleansing that are associated with patient clinical characteristics and bowel preparation-related behaviors. A model was constructed and validated to identify patients who were at high risk of inadequate bowel preparation by using six simple variables, which included male sex, diabetes, constipation, history of colorectal surgery, a high fiber diet used at 24 h prior to examination, and PC > 5 h. The clinical decision curve showed that the constructed prediction model has some clinical utility based on results from the derivation cohort and validation cohort.